Thermal and thermomechanical properties of boron nitride-filled acrylonitrile butadiene styrene (ABS) composites - László Lendvai; Daniele Rigotti (Acta Technica Jaurinensis, 2023)
The present study aims at investigating the effect of hexagonal boron nitride (hBN) nanoplatelets on the properties of acrylonitrile butadiene styrene (ABS) polymer. Composites containing 0-30 vol% hBN were prepared through batchwise melt compounding, which was followed by compression molding. Subsequently, the thermal and thermomechanical properties of the fabricated samples were investigated. The dynamic mechanical analysis (DMA) revealed that the storage modulus of the samples was markedly improved in the entire examined temperature range, while the glass transition temperature also gradually increased as a function of hBN content. According to the thermogravimetric analysis (TGA), the incorporated boron nitride particles enhanced the thermal stability of ABS composites, exhibiting a notably higher decomposition onset temperature. Additionally, the thermal conductivity of the ABS/hBN composites significantly increased by 570% when the hBN content was 30 vol%.